Impacts of dietary protein on growth performance, feed utilization, amino acid profile, activities of digestive and amino acid metabolizing enzymes of the soft‐shelled turtle (Pelodiscus sinensis). (5th February 2021) - Kou, Hongyan; Li, Feng; Zhou, Meng; Zou, Cuiyun; Zhang, Kai; Zhao, Lijuan; Miao, Yutao; Pan, Xunbin; Wang, An‐Li; Lin, Li
Abstract: The impacts of dietary protein on growth, body proximate composition, feed utilization, amino acid profile, digestive enzyme activity and amino acid metabolizing enzymes in soft‐shelled turtles ( Pelodiscus sinensis ) (initial weight: 4.02 ± 0.06 g) were measured during an 8‐week feeding trail. Six diets containing 8%, 18%, 28%, 38%, 48% and 60% (control group) fishmeal were formulated, which contained 14.38%, 20.41%, 26.19%, 32.23%, 37.63% and 45.23% protein respectively. Weight gain, mean feed intake, skirt ratio, pepsin activity of stomach, total amino acid of the muscle and crude protein levels of the whole body improved as dietary protein content increased from 14.38% to 26.19% but remained stable thereafter. The hepatosomatic index, feed conversion ratio, intestinal alpha‐amylase activity, moisture content of the whole body and serum alanine transaminase and aspartate aminotransferase activity decreased with increasing protein content up to 26.19% and then plateaued. The protein productive value and protein efficiency ratio decreased as protein content increased. Intestinal lipase activity and crude lipid levels of the whole body were unaffected by dietary protein level. Hepatic alanine transaminase and aspartate aminotransferase activity first significantly increased with increasing protein but remained stable at protein content ≥26.19%. The optimum dietary protein level for soft‐shelled turtles was in the range of 27.36%–28.46% based on weight gain, ALT activity and AST activity results.